Сoagulation hemostasis indices after hemorrhagic stroke, developed as a complication of essential hypertension - Tkachyshyn, Oleksandr (ScienceRise: Medical Science, 2021)
The aim: to determine the peculiarities of the indices of coagulation hemostasis in patients with the former occurrence of hemorrhagic stroke, developed as a complication of essential hypertension, in comparison to the hypertensive patients without complications. Materials and methods. There were formed 2 groups of patients: the main group and the comparison group. The main group included 20 patients (10 women and 10 men, middle age 52.9±1.7 (M±m) years old) who had undergone hemorrhagic stroke as a complication of essential hypertension 6 months and more previously, had no normalization of blood pressure over this period of time. The comparison group included 20 patients (10 women and 10 men, middle age 52.5±1.7 years old) suffered from essential hypertension without complications. They were matched groups according to key indicators. All the above-mentioned people underwent fasted analysis of venous blood with detection of coagulation hemostasis indices. Results. In the main and the comparison group the indices of coagulation hemostasis were the following ones, respectively: thrombin time 10.6±0.6 and 11.5±0.8 s, international normalized ratio 1.0±0.1 and 1.0±0.1, activated partial thromboplastin time 50.4±2.1 and 44.7±1.8 s (p<0.05), protein C 139.2±8.0 and 143.8±10.2 %, fibrinogen 2,4±0.4 and 2.6±0.3 g/l, soluble fibrin-monomer complexes 3.9±0.2 and 3.7±0.1 μg/mL, XIIa-dependent fibrinolysis 6.3±0.9 and 10.2±0.6 min (p<0.05), antithrombin-III 90.0±6.6 and 76.1±6.8 %. Conclusions. In the main group relatively to the comparison group there was slowing of the internal pathway of coagulation hemostasis with the quicker fibrinolysis. There was detected that 100 % of patients from the main group had at least one of the following factors out of normal values and with predisposition to bleeding: activated partial thromboplastin time >48 s, XIIa-dependent fibrinolysis <5 min, fibrinogen <2 g/l, or antithrombin-III >120 %. This information should be taken into account while prescribing the treatment, influencing hemostasis indices, in a category of hypertensive patients after hemorrhagic stroke